Implementasi Usaha Olahraga Rekreasi: M7 Tactical, Kuningan City Mall, Jakarta - Geovani, Filipus; Kusumaningrum, Dewi Ayu (Rumah Jurnal UNEJ, 2022)
The sports industry in Indonesia is being developed into a tourist visit called Sport Tourism or Recreational Sports. Tourism and sports are two disciplines combined so that they have many strengths and effects for economic growth in Indonesia. Therefore, sport tourism is a big concern of the government, private sector, sports industry and the wider community. In Indonesia, many types of sports tourism have been developed by the government. The purpose of this study was to determine the implementation of recreational sports businesses and the obstacles faced by the M7 Tactical Kuningan City Jakarta recreational sports business. The method of data analysis in this research is descriptive qualitative, the determination of the research subject is carried out using a non-probability sampling method with purposive sampling. Data was collected using observation techniques, interviews with resource persons from M7 Tactical and documentation. The results of this study indicate that M7 Tactical really understands its business as a recreational sports business that has elements of sport and fun for consumers. M7 Tactical recreational sports business consumers have active age characteristics of 19-35 years and are domiciled in Jabodetabek and not only the airsoft community but extend to the general public who have never tried and want to try shooting sports. The implementation of M7 Tactical as a recreational sport business is quite good in terms of communication, resources, attitudes, and organizational structure. Obstacles faced include the provision of airsoft units and equipment maintenance that requires quite expensive costs, the general view of the wider community regarding airsoft sports, and the Covid-19 pandemic which hampers business operations